2017
DOI: 10.1021/acs.jafc.6b04118
|View full text |Cite
|
Sign up to set email alerts
|

The Form in Which Nitrogen Is Supplied Affects the Polyamines, Amino Acids, and Mineral Composition of Sweet Pepper Fruit under an Elevated CO2 Concentration

Abstract: We investigated the effect of supplying nitrogen, as NO or as NO/NH, on the composition of fruits of sweet pepper (Capsicum annuum L. cv. Melchor) plants grown with different CO concentrations ([CO]): ambient or elevated (800 μmol mol). The results show that the application of NH and high [CO] affected the chroma related to the concentrations of chlorophylls. The concentrations of Ca, Cu, Mg, P, and Zn were significantly reduced in the fruits of plants nourished with NH, the loss of Fe being more dramatic at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…The decline in B being 15.8% at ambient CO 2 and 17.8% at 400 μmol mol −1 CO 2 , and the loss of K being 10.8% at 800 μmol mol −1 CO 2 (Table 3). These results coincide with those obtained in other experiments 15 and might be explained by the relationship of B with Ca. Tanaka 21 observed that increasing the Ca concentration in the root medium could effectively reduce the uptake of B and its accumulation in plant tissues.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The decline in B being 15.8% at ambient CO 2 and 17.8% at 400 μmol mol −1 CO 2 , and the loss of K being 10.8% at 800 μmol mol −1 CO 2 (Table 3). These results coincide with those obtained in other experiments 15 and might be explained by the relationship of B with Ca. Tanaka 21 observed that increasing the Ca concentration in the root medium could effectively reduce the uptake of B and its accumulation in plant tissues.…”
Section: Resultssupporting
confidence: 93%
“…An elevated [CO 2 ] is associated with decreased uptake of nutrients by plants, which supposes economic losses, besides compromising the availability and quality of food, thus increasing the problems of malnutrition in the world . Figure shows how plants grown under elevated [CO 2 ] had a higher net CO 2 assimilation (A CO2 ), which was more marked under control conditions (0 mmol L −1 NaCl) than in saline conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…wheat, rice, and sorghum) and vegetables (e.g. lettuce, sweet pepper, and carrot and turnip). This similarity gives us a warning that the deficiency of Fe and Zn could possibly impose an inevitable threat to human nutrition from the consumption of either grain crops or vegetables if breeders or producers continue focusing on increasing vegetable yield in the future.…”
Section: Discussionmentioning
confidence: 99%